Effects of Islamic Health Promotion Program for Hajj Pilgrim in Narathiwat Province - Sangkaew, Jarinee (Princess of Naradhiwas University Journal, 2019)
This research aimed to study effects of a health promotion program for Muslim travellers going for Hajj pilgrimage from Narathiwat province, and to study satisfaction about it. Sample was 297 pilgrims to hajj from Narathiwat province in 2018. Research instruments were the health promotion program, and a questionnaire regarding the program’s satisfaction. Cronbach’s alpha coefficient was 0.945. Data of this study were analyzed by using percentage, mean, standard deviation and slope. The study found that the sample had a lower level of health assessment (Slope value: -0.144). The sample had the following overall health level: no change in the health level (169 people, 56.9%), change from yellow level to green level (108 people, 36.4%), change from red to green (7 people, 2.4 %), change from red to yellow (8 people, 2.7 %), change from green to red (2 people, 0.7 %), and change from yellow to red (3 people, 1.0%). Satisfaction with using health promotion program was overall at a high level ( = 4.22, S.D. = 0.409).